Relationship between motivation factor with employee retention in Johor Port Authority / Ainur Syafieqa Sudirman - Sudirman, Ainur Syafieqa (Faculty of Business and Management, 2019)
This study is aimed to explore the relationship between motivational factor with employee retention in Johor Port Authority (JPA). By using a quantitative approach, there were three variables that may relate to the employee retention in an organization which are compensation, promotion as well as working condition were examined. The study collected primary data using a simple survey questionnaire which the subjects are asked to respond to the items provided. In this research, designated questionnaire was distributed to selected 108 employees in JPA at Pasir Gudang since the researcher use convenience sampling method. Data collected were subjected to statistical analysis using Statistical Package for Social Sciences (SPSS) software. In summary finding of this study reveals that compensation and promotion have significant relationship with employee retention. However, there is no significant between working condition on employee retention. Lastly, the most influence variable toward employee retention in JPA is promotion. It is therefore recommended that management of JPA should focus more on promotional opportunities to the employees since they prefer career development.